SIKAP GEREJA KATOLIK TERHADAP PERANG PASCA KONSILI VATIKAN II - Angga Satya Bhakti (Pascasarjana Universitas Hindu Indonesia, 2024)
A war is an evitable reality in human life. In a basic review war is often considered as human’s natural condition. War is believed as evitable and natural. Further observation states that war is an unnatural situation. The theory of fair war and war law is the logical consequence towards this circumstance. The Church, as a part of the world citizen, also has view and outlook towards war. Post the second Vatican Council, the Church has opened itself more towards the problems happen in the world in order to take part in the attempt to resolve the world’s problems, including war. The Church issued the teaching of the Church via encyclical and the documents of the Church. This research is conducted to give the depiction of the Church’s view towards war. The method used in this research is literature review with the references from journal, books and Church’s directives, such as encyclical or the social teaching of the Church. This research is expected to be capable of being a guideline for the Christians in behaving towards war.